Analisis Residu Profenofos dalam Tanah Secara Voltammetri Lucutan Menggunakan Elektroda Grafit - Tanik, Anita Florida (Universitas Airlangga, 2015)
This study aimed to determine the ability of stripping voltammetry using graphite electrodes in analyzing profenofos. In this study, profenofos was accumulated at 0.3 V (V, vs Ag/AgCl) for 60 seconds at pH 5. Subsequently, the optimum conditions were used to analyze profenofos 10 ppb. The study yielded a correlation coefficient (r) of calibration curve of 0.9967; precision between of 95.69 â 99.14%; sensitivity of 32.64 Î¼A/ppb; detection limit of 0.0038 ppb and accuracy of 94 â 115%.Keywords : profenofos, graphite electrodes, voltammetry